1959
DOI: 10.1111/j.1550-7408.1959.tb04361.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Ingestion by the Rumen Ciliates Entodinium and Diplodinium

Abstract: SYNOPSIS. In cattle fed a high‐starch diet, species of Entodinium and Diplodinium ingested associated ruminal bacteria. Stained preparations of diluted rumen contents showed Entodinium caudatum, E. minimum, E. dubardi, (syn. E. simplex), E. longinucleatum, E. bursa, E. nanellum, E. exiguum, and E. vorax contained gram‐positive diplococci. Starch grains with adherent gram‐positive diplococci were observed within Entodinium spp. Diplodinium ecaudatum forma ecaudatum, D. ecaudatum forma caudatum, D. neglectum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1960
1960
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The predatory ciliate action on bacteria (Coleman, 1975), which favours the metabolic activity of bacteria (Kurihara et al, 1968 ;Thomas, 1973 ;Senaud, 1978, 1979 ; Demeyer and Van Nevel, 1979), could be lower with I than with E ciliates (Gutierrez, 1958 ;Gutierrez and Davis, 1959). In the presence of P or E, the depressive action of I on digestion disappears.…”
Section: Resultsmentioning
confidence: 99%
“…The predatory ciliate action on bacteria (Coleman, 1975), which favours the metabolic activity of bacteria (Kurihara et al, 1968 ;Thomas, 1973 ;Senaud, 1978, 1979 ; Demeyer and Van Nevel, 1979), could be lower with I than with E ciliates (Gutierrez, 1958 ;Gutierrez and Davis, 1959). In the presence of P or E, the depressive action of I on digestion disappears.…”
Section: Resultsmentioning
confidence: 99%
“…When the fresh rumen fluid was replaced by autoclaved rumen fluid bacteria were still present, and it is likely that these were chloramphenicol resistant. I n view of the finding of Gutierrez & Davis (1959) that Entodinia spp. ingest Streptococcus bovis and possibly require that bacterium for growth, it is possible that the chloramphenicol in the present experiments suppressed bacteria harmful to the protozoa while allowing favourable bacteria to survive.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gutierrez & Davis (1959) were able to isolate only 3-10 Streptococcus bovis organisms per ciliate, as compared with the 100-150 bacteria which were visible microscopically. The ciliates were also shown to ingest 8. bovis and it was suggested that the protozoa might have been digesting the bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep rumen Entodiniomorphid protozoa freshly isolated from the rumen (Gutierrez & Davis, 1959) or grown in vitro (Coleman, 1962) contain bacteria in their gastric sacs. However, Gutierrez & Davis (1959) were able to isolate only 3-10 Streptococcus bovis organisms per ciliate, as compared with the 100-150 bacteria which were visible microscopically.…”
Section: Introductionmentioning
confidence: 99%